نسبة مساهمة بعض أوجه القوة العضلية وعلاقتها بدقة التمريرات (القصيرة والمتوسطة والطويلة) لدى لاعبي نادي كربلاء بكرة القدم - حاتم, ميثم فخري; الحسين, صاحب عبد; محمد, خالد (Sulaimani Journal for Humanities, 2018)
Summary In order to make the game progress and deepen, it is necessary to mix the other sciences in order to upgrade the players to the upper levels, and it is not easy to reach those levels unless the methods and means are used to enable access to solutions and alternatives that enable the coach to overcome the obstacles encountered during the training process The pass is the most important offensive skills that enable the team to win if he master this skill as required, accuracy is important in which the team can control the game throughout the game and control the pitch by securing the ball to the right place before being exposed For cutting by the opponent. However, the researchers used the descriptive approach in its surveying style and correlative relationships . The research population involved (24) players and the researchers excluded (3) goalkeepers' and ( 3) players who were involved into pilot experiment for muscle strength and accuracy of passes tests. The sample finally was a (18) players represented (91.42%) of the population. Finally, the researchers recommended that the need to work on the development of the skill aspect especially the passing, which is the basis of e football, and put them in daily training modules. As well as using the physical and skill tests to assess the level of players before entering the competition.